Removal of emulsified and dissolved diesel oil from high salinity wastewater by adsorption onto graphene oxide. Issue 3 (June 2019) - Diraki, Ahmad; Mackey, Hamish R.; McKay, Gordon; Abdala, Ahmed
Graphical abstract: Highlights: Graphene oxide was used for adsorption of diesel from oil-water emulsion. A high capacity of 1335 mg/g was achieved. Adsorption capacity increased under increasing salinity, tested up to 100 g/L NaCl. Adsorption showed extremely rapid kinetics reaching 90% of capacity within 4 min. Fixed-bed column tests demonstrate compact adsorption system with good regeneration. Abstract: Large quantities of oily wastewaters are produced globally from oil extraction and refining industries containing low concentrations of dissolved and finely emulsified oils. These waters are difficult to treat within a small footprint as often necessary, especially on offshore sites, and often contain high salinity making many treatment methods ineffective. In this study the use of graphene oxide (GO) as an adsorbent is investigated using diesel as a representative oil. GO demonstrated a high adsorption capacity of 1335 mg/g according to the Freundlich isotherm and based on theoretical surface area was likely due to limited multi-layer adsorption. Increasing salinity to 1% increased adsorption capacity by 75%, remaining constant thereafter, confirming the suitability for the material for saline produced water remediation. Adsorption was extremely rapid, reaching more than 90% of the equilibrium capacity within 4 min, and was represented best by a pseudo-second order kinetic model. Fixed bed column tests confirmed the ability for excellent removal capacities under a short contact time and good regeneration, indicating the potential of GO for industrial oil-water emulsion separation applications. Based on careful analysis of isotherm and kinetic data, in conjunction with theoretical considerations, a rapid multi-layer physisorption mechanism, influenced by GO agglomeration, is proposed.